Feasibility of using impedance-based damage assessment for pipeline structures. - Park, Gyuhae
This paper presents the feasibility of using an impedance based health monitoring technique in monitoring a critical civil facility. The objective of this research is to utilize the capability of the impedance method in identifying structural damage in those areas where a very quick condition monitoring is urgently needed, such as in a post earthquake analysis of a pipeline system. The basic principle behind this technique is to utilize high frequency structural excitation (typically greater than 30 kHz) through surface bonded piezoelectric sensors/actuators to detect changes in structural point impedance due to the presence of damage. Real time damage detection in pipes connected by bolted joints was investigated and the capability of the impedance method in tracking and monitoring the integrity of the typical civil facility has been demonstrated. Data collected from the tests illustrates the capability of this technology to detect imminent damage under normal operating conditions and immediately after a natural disaster.
Keywords: Damage; Damage assessment; Non-destructive measurement; Impedance; Piezoelectric materials; Pipe joints